Peran Teknologi dalam Penggunaan Media Belajar Bagi Siswa Sekolah Dasar - Diyah Nur Septiyaningsih; Najma Alkhayya; Nana Mardiana; Didik Tri Setiyoko (Journal on Education, 2025)
The rapid development of technology in this global era has a significant impact on the world of education. The demands of the era that continue to develop encourage the education sector to always adapt to technological advances in order to improve the quality of learning. In this case, teachers are expected to be able to create interesting learning experiences in order to compete with the appeal of technology and entertainment outside the classroom. Therefore, the lecture method needs to be reduced, especially in learning that emphasizes process skills and active learning. Teachers must be more creative in utilizing technology, especially learning media, to increase the effectiveness and appeal of learning in schools. This study aims to examine the role of technology in education, with a qualitative approach through literature studies. The results of the study indicate that educational technology has a very important and inseparable role in the learning process. Thus, the development of technology and education complement each other, collaborate, and contribute to the progress of education it self.